Do oarsmen have asymmetries in the strength of their back and leg muscles? - Parkin, S.; Nowicky, A. V.; Rutherford, O. M.; McGregor, A. H. (Journal of Sports Sciences, 2001)
The aim of this study was to establish whether asymmetry of the strength of the leg and trunk musculature is more prominent in rowers than in controls. Nineteen oarsmen and 20 male controls matched for age, height and body mass performed a series of isokinetic and isometric strength tests on an isokinetic dynamometer. These strength tests focused on the trunk and leg muscles. Comparisons of strength were made between and within groups for right and left symmetry patterns, hamstring: quadriceps ratios, and trunk flexor and extensor ratios. The results revealed no left and right asymmetries in either the knee extensor or flexor strength parameters (including both isometric and isokinetic measures). Knee extensor strength was significantly greater in the rowing population, but knee flexor strength was similar between the two groups. No difference was seen between the groups for the hamstring: quadriceps strength ratio. In the rowing population, stroke side had no influence on leg strength. No differences were observed in the isometric strength of the trunk flexors and extensors between groups, although EMG activity was significantly higher in the rowing population. Patterns of asymmetry of muscle activity were observed between the left and right erector spinae muscles during extension, which was significantly related to rowing side (P < 0.01). These observations could be related to the high incidence of low back pain in oarsmen.